2021
DOI: 10.1177/14574969211007036
|View full text |Cite
|
Sign up to set email alerts
|

Patient Self-Assessment and Acoustic Voice Analysis in Screening of Postoperative Vocal Fold Paresis and Paralysis

Abstract: Background and Aims: The aim of this study was to evaluate the utility of two items in vocal fold paresis and paralysis screening after thyroid and parathyroid surgery: patient self-assessment of voice using the Voice Handicap Index and computer-based acoustic voice analysis using the Multi-Dimensional Voice Program. Materials and Methods: This was a prospective study of 181 patients who underwent thyroid or parathyroid surgery over a 1-year study period (2017). Preoperatively, all patients underwent laryngosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Literature findings are in accordance with the results of this study [13-15, 20, 33]. Heikkinen et al [33] found that self-assessment with VHI has a high specificity for vocal fold paresis/paralysis. The works of D'Alatri et al [20] and Schindler et al [14] show, in accordance with this study, that the highest results achieved were on the physical subscale both before and after therapy, whereas the lowest scores achieved were on the emotional subscale.…”
Section: Discussionsupporting
confidence: 92%
“…Literature findings are in accordance with the results of this study [13-15, 20, 33]. Heikkinen et al [33] found that self-assessment with VHI has a high specificity for vocal fold paresis/paralysis. The works of D'Alatri et al [20] and Schindler et al [14] show, in accordance with this study, that the highest results achieved were on the physical subscale both before and after therapy, whereas the lowest scores achieved were on the emotional subscale.…”
Section: Discussionsupporting
confidence: 92%